SISTEM KOORDINASI DAN KECERDASAN BUATAN UNTUK STRATEGI BERTANDING PADA ROBOT SOCCER - Widagdo, Prabancoro Adhi Catur; Rachmawati, Ermita Dwi; Chulafaurrosyda, Renita; Sulistijono, Indra Adji (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This research presents an autonomous control system of multi-agent robot soccer. The control system is used to realize the holonomic movement of 2 agent robot to make their trajectory. A movement of multi-agent robot soccer is based on visualization by a camera which located above the robot field. A visualization involves process of color detection, such as marker detection and ball detection. The results will processed into coordinate data to make conversion become angle data, distance data and heading angle of agent robot. The generated data will broadcast serially and the agent robot will receive the appropriate data to make a movement. The movement data will processed by the Distribution of Vector Equation. The resulting motion are linear motion, angular motion, and mixed of linear and angular. The results of the system that have been made are work properly, which have a record of agent robot movement, the error data is 1,44%. Keywords: Broadcast, Color Detection, Distribution of Vector, Holonomic, Multi-agent Robot Soccer, Trajectory.